PENERAPAN DALUWARSA DALAM PENETAPAN PENERBITAN SURAT TAGIHAN PAJAK BUNGA PENAGIHAN - Suparna Wijaya; Urlich Zwingly Putra Pardede (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2020)
The expiration of the issuance of STP Bunga Penagihan is not clearly regulated in the Law on General Provisions and Tax Procedures (UU KUP). Then the Peraturan Pemerintah 74 of 2011 was issued which should explain further, but has not yet provided legal certainty. PP 74 of 2011 states that the period of issuance of STP and SKPKB is the same, namely 5 years from the end of the tax year or part of the tax period, then there is no explanation of what type of STP is meant, so there are so many interpretations from various parties that cause bias law. This study aims to determine the legal basis for the issuance of STP Bunga Penagihan, the implementation of the STP Bunga Penagihan at the Tax Office and the various interpretations of the resource persons related to this research. This research is a qualitative research using literacy methods and field research in the form of interviews. This research gives results where there are many legal bases governing the issuance of STP Bunga Penagihan but do not clearly state the period of issue. This ambiguity can also be resolved with the views of the staff of the Directorate General of Taxes of the Republic of Indonesia and other informants who tend to be similar regarding the period of issuance of STP Bunga Penagihan. Case studies of relevant court decisions are also described in this journal.